IDENTIFIKASI POTENSI NILAI EKONOMI HASIL HUTAN BUKAN KAYU DI UPT KPH BULUSARAUNG (Studi Kasus Resort Kabupaten Pangkep) - Aisyah putri Putri; Andi Nur Imran; Nirawati Nirawati; Andi Khairil A.Samsu (Jurnal Eboni, 2021)
Types of non-timber forest products found in UPT KPH Bulusaraung case study in Pangkep Regency is bamboo, pine resin, candlenut, honey and sugar palm. The purpose of this study was to determine the types of non-timber forest products at UPT KPH Bulusaraung (a case study of Pangkep Regency resort), and to analyze the potential economic value of non-timber forest products at UPT KPH Bulusaraung (a case study of Pangkep Regency resort). The method used is the purposive sampling technique in the form of a 20 m x 20 m plot with the object of observation of non-timber forest product types, and the interview was conducted using a questionnaire method. The types of non-timber forest products found in the UPT KPH Bulusaraung area (a case study of Pangkep Regency resort) are bamboo, pine resin, candlenut, honey, and palm sugar and The 2 economic value of timber forest products found located in the UPT KPH Bulusaraung area (a case study of Pangkep Regency resort), the highest potential economic value is found in pine resin NTFPs (Monotropahypopitys) which are produced per year amounting to Rp. 147,420,000,000 with a presentation value of 98.59% and the lowest potential economic value is found in the lowest NTFP type (Arenga pinnata (WURMB) MERR)) which is produced annually at Rp. 45,000,050 from the calculation of Potential Economic Value (PE) with a presentation of 0.03%. Keywords: Potentian, Economic Value, Non-timber Forest Product